Flesh in the age of reason: the modern foundations of body and soul, and a dialogue by Jeremy Collier (1695) : letter to the editor - Jarius, Sven; Wildemann, Brigitte (Brain, 2013)
Sir,In Volume 127, Issue 10 of Brain a review of the late Roy Porter’s last, great book Flesh in the age of reason (2003) appeared (Myer, 2004). Porter, who died in 2002, was Professor in the Social History of Medicine at the Wellcome Trust Centre for the History of Medicine at University College, London, and Editor of the Cambridge illustrated history of medicine (Browne, 2003). Summarizing Porter’s chapter on Samuel Johnson (entitled Johnson and incorporated minds), the author of the review wrote: ‘Porter tells us that Johnson mocks attempts to locate the soul within the body: the brain is a “quagmire”, “clammy” and, quoting high Church divine Jeremy Collier, “an odd sort of bog for fancy to paddle in”. This is all charmingly picturesque, but my copy of Johnson’s Dictionary does not confirm; I find nothing of the sort under “soul” or “brain” and no mention of Collier. Has Porter misremembered or is he quoting another source? Porter’s footnotes tended to be chaotic until final revision. He died before they could be systematized and his present editors decided to do without them.’
Gesehen am 25.03.2021